Neurovascular Unit Dysfunction and Neurodegenerative Disorders - Yu, Xing; Ji, Caihong; Shao, Anwen (Frontiers in Neuroscience, 2020)
The neurovascular unit (NVU), comprised of vascular cells, glial cells and neurons, is the minimal functional unit of the brain. The NVU maintains integrity of the blood-brain barrier (BBB) and regulates supply of the cerebral blood flow (CBF), both of which are keys to maintaining normal brain function. BBB dysfunction and a decreased CBF are early pathophysiological changes in neurodegenerative disorders, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS). In this review, we primarily focus on the NVU in AD as much research has been performed on the connection between NVU dysfunction and AD. We also discuss the role of NVU dysfunction in the pathophysiological mechanisms of PD and ALS. As most neurodegenerative diseases are difficult to treat, we discuss several potential drug targets that focus on the NVU that may inform novel vascular-targeted therapies for AD, PD and ALS.